On juridical ideal of citizenship. The origins of the modern concept of citizenship - Hrehorowicz, Arleta (Studia Iuridica Toruniensia, 2017)
Towards the end of XVIII century the liberal concept of human rights has been formed. It assumed, inter alia, that individual is a subject of ‘some’ catalogue of natural rights and this rights and obligations are deXning the scope of state power. At the same time the model of modern notion of the citizen and citizenship has been implemented. Originate of this process is a subject of this study in contrast to the aim of this article, which is capturing time, place and background of doctrinal formation of civil society’s modern idea. Therefore the topic of this work is the citizen – and, consequently, its relation to the state (in the sense of a certain formal and legal order) – considered from a historical perspective on a meta-legal level. This paper provides nformation on the time and place of the formation of the democratic government, as well as on the ideological background of the origins of the modern concept of citizenship.